Optimization of systems reliability - Tillman, Frank A.; Hwang, Ching-Lai; Kuo, Way (Industrial engineering, 1980)
The methods used to optimize systems reliability problems are comprehensively presented and discussed in this book, the fiurst attempt to gather together a concise and comprehensible overview of this important body of techniques and problems. Both reliability engineers and the community of researchers and students involved in operations research will find this to be the most complete account of the subect to date.